The changing role of universities in the German research system: engagement in regional networks, clusters and beyond - Knut Koschatzky; Thomas Stahlecker (Fraunhofer Institute for Systems and Innovation Research ISI, 2010)
In Germany, but in other countries as well, a trend towards a regionalisation in technology and innovation policy is clearly evident. This triggers the expectation towards universities to establish regional ties and networks and to exploit the advantages of spatial proximity to other research institutes, to industry and to policy and regional administration. It is the objective of this paper to analyse the changing role of universities as driving force in the development of new modes and models of collaboration both with industry and with other research organisations. Starting from the triple-helix and the entrepreneurial university approach, the role of universities in regional research and innovation policy will be discussed. On this background, three case studies will be presented in order to illustrate how German universities deal with the expectations of a stronger regional integration and embeddedness.
urn:nbn:de:0011-n-1539456
Keywords: 330; university governance; research policy; regional collaboration; new modes of cooperation; public-private partnerships